Provenance of clay-sized detrital sediments in the North Sea and the Skagerrak region based on radiogenic Nd-Sr-Hf isotopes and clay mineral compositions: assessing the impact of coastal and seabed erosion - Lenz, Nina; Spiegel, Timo; Hathorne, Ed; Wallmann, Klaus; Eisenhauer, Anton; Frank, Martin (Frontiers in Marine Science, 2024)
The Skagerrak basin represents the main sink area for fine-grained sediment in the North Sea region and constitutes a natural deposition center for sediments that are supplied from the Atlantic, the Baltic Sea and the surrounding continental margins and coasts. However, the exact sources and their proportional contributions to the North Sea sediments and to the Skagerrak deposits are not well understood. To trace the predominant sources of the sediment and to gain a better understanding of the sedimentary processes in the North Sea and the Skagerrak basin, radiogenic Sr, Nd, and Hf isotope signatures and clay mineral compositions of the detrital clay fraction of surface sediment samples from the North Sea, the Scandinavian margins and the Baltic Sea were measured. The results indicate that the major source for Skagerrak clay-size sediments is the northern North Sea but Scandinavia as well as the southern North Sea including the southern England coast also contribute material. Seabed and coastal erosion in the northern North Sea are enhanced by the inflowing Atlantic Currents, which provide the Skagerrak with high amounts of clay size sediments. In contrast, the southern North Sea, the Baltic Sea and mid-European rivers such as Weser, Elbe and Ems are only minor contributors. As Skagerrak deposits are dominated by clay sized material (up to 60%), the reconstructed sediment processes in this study deviate from findings in previous sediment budget studies, which were based on both clay and silt fraction and indicated predominant influences from the southern North Sea. These results highlight that coastal and seabed erosion in the North Sea is a previously underestimated source of fine-grained sediments for depocenters in the entire North Sea. With regard to climate change, the global sea-level rise will likely enhance erosional processes and can therefore significantly influence the sediment budget of the entire North Sea.